Bleeding Risk in Patients with Cancer - Englisch, Cornelia; Vladic, Nikola; Ay, Cihan (Hämostaseologie, 2024)
The hemostatic system and cancer display a tight interconnection, and hemostatic imbalance frequently occurs in patients with cancer. While extensive knowledge about thrombotic risk has been generated, less is known about bleeding risk and associated risk factors. However, bleeding risk is of high significance as patients with cancer frequently receive therapeutic anticoagulation for various indications and/or are candidates for primary thromboprophylaxis. The risk of bleeding in patients with cancer is variable and difficult to assess in clinical practice. Certain clinical settings such as hospitalization, specific underlying risk factors (e.g., tumor type), and medications (e.g., anticoagulation) can contribute to the individual bleeding risk of a patient with cancer. In addition, some dynamic factors such as platelet count or kidney function have an impact. Particularly, data on baseline risk of bleeding are lacking to allow for risk assessment in cancer patients without anticoagulation. In contrast, risk assessment models for the prediction of bleeding events in cancer patients receiving anticoagulation have been developed; however, these have yet to be validated. The recognition of the importance of bleeding risk in cancer patients is growing, leading to an increasing number of studies investigating and reporting bleeding complications. As study designs and reporting of bleeding events vary, it is challenging to offer a clear synthesis of evidence. In this narrative review, we provide an overview of currently available data about incidence, risk factors, and clinical impact of bleeding events in patients with cancer, and critically review risk assessment models for bleeding in cancer patients during anticoagulant therapy.
Keywords: hemorrhage; major bleeding; cancer; risk